Recommendations for tick-borne encephalitis vaccination from the Central European Vaccination Awareness Group (CEVAG) - (:unkn) unknown (TAYLOR & FRANCIS INC, 2013)
Tick-borne encephalitis (TBE) is a viral neurological zoonotic disease transmitted to humans by ticks or by consumption of unpasteurised dairy products from infected cows, goats, or sheep. TBE is highly endemic in areas of Central and Eastern Europe and Russia where it is a major public health concern. However, it is difficult to diagnose TBE as clinical manifestations tend to be relatively nonspecific and a standardised case definition does not exist across the region. TBE is becoming more important in Europe due to the appearance of new endemic areas. Few Central European Vaccination Awareness Group (CEVAG) member countries have implemented universal vaccination programmes against TBE and vaccination coverage is not considered sufficient to control the disease. When implemented, immunization strategies only apply to risk groups under certain conditions, with no harmonised recommendations available to date across the region. Effective vaccination programmes are essential in preventing the burden of TBE. This review examines the current situation of TBE in CEVAG countries and contains recommendations for the vaccination of children and high-risk groups. For countries at very high risk of TBE infections, CEVAG strongly recommends the introduction of universal TBE vaccination in children > 1 y of age onwards. For countries with a very low risk of TBE, recommendations should only apply to those traveling to endemic areas. Overall, it is generally accepted that each country should be free to make its own decision based on regional epidemiological data and the vaccination calendar, although recommendations should be made, especially for those living in endemic areas.
Keywords: tick-borne encephalitis; TBE vaccination; recommendations; CEVAG; Central Europe; VIRUS; TBE; PREVENTION; INFECTION; VACCINES; HUNGARY; SAFETY